Immune responses in cattle vaccinated against contagious bovine pleuropneumonia: preliminary results - Mbithi, F.; Wesonga, H.O.; Thiaucourt, Francois; Taracha, E.L.N. (Food and Agriculture Organization of the United Nations, 2004)
Contagious bovine pleuropneumonia (CBPP) is one of the most important transboundary animal diseases in Africa. In recent years, CBPP has been found in countries like Botswana from where it was previously eradicated (Amanfu et al., 1998). There is growing evidence to indicate that the incidence of the disease is increasing in endemic areas. These recent increases can be attributed to uncontrolled movement of cattle, poor disease control strategies and application of sub-standard vaccines (FAO, 2000; Masiga, 1996). There is sufficient consensus that efficacious vaccines could contribute substantially to an integrated control program for CBPP (Anonymous, 2000; Tuslane et al., 1996). This would involve improvement of existing and Development of a new generation of vaccines. This study is aimed at investigating the immunogenicity and efficacy of two different vaccines against CBPP. The T1 44 vaccine strain and a saponin formulated inactivated virulent strain of Mycoplasma mycoides subspecies mycoides small colony (Mmm SC), strain 237, were used.